ENERGY USE PATTERN OF SELECTED COMMERCIAL POULTRY FARMS IN OGUN STATE, NIGERIA - BABALOLA, Ayoola A.; SANUSI, Abisola O.; ADETIFA, Babatunde O.; ADEYEMI, Hezekiah O.; OLATUNDE, Olanrewaju B. (Journal of Engineering Science (Chişinău), 2020)
Energy represents an important component of agriculture and essential to the sustainable production of poultry meat and egg. Despite several efforts at ensuring self- sufficiency in the local production of poultry products through the provision of fast-growing disease-resistant breeds, high energy feeds and improved health care amenities, little efforts have been made in the estimation of critical energy needs of the poultry industry in Nigeria. This study investigated the daily energy utilization pattern of 10 selected commercial poultries farms in a major agricultural state in the country, Ogun State Nigeria. The study was carried out using a structured questionnaire, oral interview, and site observation. The predominant sources of energy alongside the mean daily energy were; electricity (37053 MJ, 36%), Diesel (2868 MJ, 30%), petrol (606.30 MJ, 29%), human labour (76.23 MJ, 4%) and other sources of energy (13.16 MJ, 1%). There was a weak relationship between the total energy consumed per day and the poultry capacity (R2 = 0.3772). The Anova of Energy Use, feed consumption, bird weight and egg production showed no significant difference across the farms (P=0.301886, α=0.05). Feeding, water pumping, ventilation and lighting (heating) were the major energy consumers on the farm.